A review on modified carbon materials as promising agents for hydrogen storage. (1st June 2018) - Rostami, Siroos; Pour, Ali Nakhaei; Izadyar, Mohammad
Carbon materials have been regarded as promising agents for hydrogen storage because of properties such as their light weight, acceptable affinity of carbon for hydrogen and high specific surface area. We can identify many different carbon materials which have been studied extensively such as activated carbons (AC) graphene sheets (GS), carbon nanotubes (CNTs) and other derivative carbon materials derived from theoretical and experimental methods such as g-C3N4, graphyne and carbon nanolayer. These materials can be modified by additional ingredients like free metals, metal oxides, and alloys to improve their hydrogen storage capacity. In this short review article, we attempt to introduce new, reliable, complete and categorised data for researchers concentrating on articles from the last five years (2013–2017) relating to hydrogen storage.